Implementation of Enterprise Resource Planning (ERP) in Indonesia to Increase the Significant Impact of Management Control Systems - Rahardja, Untung; Ramadan, Ahmad (APTISI Transactions on Management (ATM), 2023)
To improve the Management Control Systems, an accidental sampling (non-probability sampling) method is used to apply Enterprise Resource Planning (ERP). Export and import service companies in the Jakarta Capital City area became the population in this study, with the total sample used is 100 respondents. 3 (three) variables that are the primary key of this research are Management Control System (X1) is an independent variable, and ERP implementation (Y) is classified as a related variable. The results obtained after this study's test indicate that ERP implementation (Y) is significantly influenced by the Management Control System (X1). There are several compromises in implementing an ERP (Enterprise Resource Planning) system in Indonesia. These factors exist in both the manufacturing and service industries. These have been identified as staffing issues where users do not understand how to use the  ERP system. This lack of understanding leads to the implementation of non-optimized ERP due to the lack of education and learning about system usage and operational know-how. ERP is an evolution of Enterprise Resource Planning II (MRP II), a further development of Material Requirements Planning (MRP). ERP includes a warehouse management package as a first step, which is the supply control used in manufacturing or servicing products. The second phase of material requirements planning is the ERP route. In addition, the third phase of MRPII was the development of closed-loop MRP. ERP will emerge as Phase 4, an extension of MRP II and business processes. Extended ERP is the fifth phase of ERP, was introduced in 2000 and is much more complex than previous ERP.